2022
DOI: 10.1093/asjof/ojac047
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Open-Label, Multicenter, Real-World Study of VYC-17.5L Hyaluronic Acid Dermal Filler in the Lips

Abstract: Background Hyaluronic acid (HA) injectable gels are used to define, enhance, and volumize facial regions, such as the lips, a common treatment area. Objective Evaluate the effectiveness and safety of the HA injectable gel Juvéderm Volift (Allergan, Irvine, CA) with Lidocaine (VYC-17.5L) for lip augmentation in real-world clinical practice. Methods This prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…A high responder rate (66.7%) was sustained at the six-month follow-up visit. Interestingly, a previous study evaluating the effectiveness and safety of a traditional HA-based filler (VYC-17.5L) for lip augmentation found that 93.2% of participants were responders at one month; however, this percentage declined significantly to 39% at 12 months [ 8 ]. This suggests that the clinical efficacy of HA fillers crosslinked with reduced amounts of BDDE, as observed in our study, is comparable to commonly used HA fillers in terms of LPS2 increase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A high responder rate (66.7%) was sustained at the six-month follow-up visit. Interestingly, a previous study evaluating the effectiveness and safety of a traditional HA-based filler (VYC-17.5L) for lip augmentation found that 93.2% of participants were responders at one month; however, this percentage declined significantly to 39% at 12 months [ 8 ]. This suggests that the clinical efficacy of HA fillers crosslinked with reduced amounts of BDDE, as observed in our study, is comparable to commonly used HA fillers in terms of LPS2 increase.…”
Section: Discussionmentioning
confidence: 99%
“…The primary efficacy endpoint was the post-procedural increase in the investigator-reported LFS2 (0 = minimal, 1 = mild, 2 = moderate, 3 = marked, and 4 = very marked) compared with baseline [ 19 ]. In addition, patients who showed an improvement of at least one point on the LFS2 compared with baseline were considered as responders [ 8 ]. Secondary efficacy endpoints included 1) investigator- and subject-reported Global Aesthetic Improvement Scale (GAIS), rated on a 5-point scale (0 = much worse; 1 = worse; 2 = no change; 3 = improved; 4 = much improved); 2) subject-reported assessment of natural look and feel of lips, rated on a 5-point Likert Scale (0 = not at all to 4 = very much); 3) subject-reported Happiness Measure Scale (HMS), an instrument used to rate subjective well-being on a 11-point Likert Scale (0 = not happy at all to 10 = extremely happy) [ 8 , 18 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lip filling with hyaluronic acid is a non-surgical aesthetic procedure that aims to increase lip volume and improve lip contour. 1 Hyaluronic acid is a molecule naturally present in the human body, responsible for maintaining the hydration and elasticity of the skin and connective tissue. Due to its properties, hyaluronic acid has been widely used in aesthetic medicine for facial rejuvenation and volume enhancement in different body areas, including the lips.…”
Section: Introductionmentioning
confidence: 99%